If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2x^{2}+ -24x = -2x^{2}+ -7x + -18 Reorder the terms: -24x + 2x^{2}= -2x^{2}+ -7x + -18 Reorder the terms: -24x + 2x^{2}= -18 + -7x + -2x^{2}Solving -24x + 2x^{2}= -18 + -7x + -2x^{2}Solving for variable 'x'. Reorder the terms: 18 + -24x + 7x + 2x^{2}+ 2x^{2}= -18 + -7x + -2x^{2}+ 18 + 7x + 2x^{2}Combine like terms: -24x + 7x = -17x 18 + -17x + 2x^{2}+ 2x^{2}= -18 + -7x + -2x^{2}+ 18 + 7x + 2x^{2}Combine like terms: 2x^{2}+ 2x^{2}= 4x^{2}18 + -17x + 4x^{2}= -18 + -7x + -2x^{2}+ 18 + 7x + 2x^{2}Reorder the terms: 18 + -17x + 4x^{2}= -18 + 18 + -7x + 7x + -2x^{2}+ 2x^{2}Combine like terms: -18 + 18 = 0 18 + -17x + 4x^{2}= 0 + -7x + 7x + -2x^{2}+ 2x^{2}18 + -17x + 4x^{2}= -7x + 7x + -2x^{2}+ 2x^{2}Combine like terms: -7x + 7x = 0 18 + -17x + 4x^{2}= 0 + -2x^{2}+ 2x^{2}18 + -17x + 4x^{2}= -2x^{2}+ 2x^{2}Combine like terms: -2x^{2}+ 2x^{2}= 0 18 + -17x + 4x^{2}= 0 Factor a trinomial. (2 + -1x)(9 + -4x) = 0## Subproblem 1

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2## Subproblem 2

Set the factor '(9 + -4x)' equal to zero and attempt to solve: Simplifying 9 + -4x = 0 Solving 9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 0 + -9 -4x = 0 + -9 Combine like terms: 0 + -9 = -9 -4x = -9 Divide each side by '-4'. x = 2.25 Simplifying x = 2.25## Solution

x = {2, 2.25}

| 30x^3-9x^2-3x=0 | | x^2+4=17 | | (x^3+2x+3x+6)= | | (2x^3+3)= | | (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= | | 10y^2+33y+20=0 | | y^3+8y^2+16y=0 | | x^2+4x-60=0 | | 14x^2-5x=0 | | (x^3+y^5)(x^3-y^5)= | | 5x^2+11x+1=0 | | y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions
- How to solve complicated linear equation